Using immunisation caregiver journey interviews to understand and optimise vaccination uptake: lessons from Sierra Leone. Issue 5 (27th May 2021) - Jalloh, Mohamed F; Hickler, Benjamin; Parmley, Lauren E; Sutton, Roberta; Kulkarni, Shibani; Mansaray, Anthony; Eleeza, Oliver; Patel, Palak; Wilhelm, Elisabeth; Conklin, Laura; Akinjeji, Adewale; Toure, Mame; et al.
Abstract : Quantitative and qualitative assessments have revealed diverse factors that influence the uptake of childhood immunisation services and shed light on reasons for vaccination delays and refusals. UNICEF and partner organisations developed the Immunisation Caregiver Journey Framework as a novel way to understand caregiver experiences in accessing and receiving immunisation services for children. This framework aims to help immunisation programmes identify vaccination barriers and opportunities to improve vaccination uptake by enhancing the overall caregiver journey in a systems-focused manner, using human-centred design principles. In this paper, we adapt the framework into a flexible qualitative inquiry approach with theoretical guidance from interpretative phenomenology. We draw from the implementation experiences in Sierra Leone to inform methodological guidance on how to design and implement the Immunisation Caregiver Journey Interviews (ICJI) to understand the lived experiences of caregivers as they navigate immunisation services for their children. Practical guidance is provided on sampling techniques, conducting interviews, data management, data analysis and the use of data to inform programmatic actions. When properly implemented, the ICJI approach generates a rich qualitative understanding of how caregivers navigate household and community dynamics, as well as primary healthcare delivery systems. We argue that understanding and improving the caregiver journey will enhance essential immunisation outcomes, such as the completion of the recommended vaccination schedule, timeliness of vaccination visits and reduction in dropouts between vaccine doses.